Māwhitiwhiti Aotearoa: Phylogeny and synonymy of the silent alpine grasshopper radiation of New Zealand (Orthoptera: Acrididae) - Trewick, Steven A.; Koot, Emily M.; Morgan-Richards, Mary (Zootaxa, 2023)
Aotearoa New Zealand has a fauna of endemic alpine grasshoppers, consisting of thirteen species distributed among four genera. The many re-classifications of species within this group and the presence of species complexes highlight the uncertainty that surrounds relationships within and between these genera. High-throughput Next Generation Sequencing was used to assemble the complete mitochondrial genomes, 45S ribosomal cassettes and histone sequences of New Zealand’s four endemic alpine genera: Alpinacris, Brachaspis, Paprides and Sigaus. Phylogenetic analysis of these molecular datasets, as individual genes, partitions and combinations returned a consistent topology that is incompatible with the current classification. The genera Sigaus, Alpinacris, and Paprides all exhibit paraphyly. A consideration of the pronotum, epiphallus and terminalia of adult specimens reveals species-specific differences, but fails to provide compelling evidence for species groups justifying distinct genera. In combination with phylogenetic, morphological and spatial evidence we propose a simplified taxonomy consisting of a single genus for the māwhitiwhiti Aotearoa species radiation.